New insight into the intravenous immunoglobulin treatment in Multisystem Inflammatory Syndrome in children and adults - Chih-Jen Chen; Hsu-Yen Kao; Ching-Hua Huang; Chia-Jung Li; Cheng-Hsien Hung; Su-Boon Yong (BMC, 2024)
Abstract Within 6 months of the coronavirus pandemic, a new disease entity associated with a multisystem hyperinflammation syndrome as a result of a previous infection with the SARS-CoV-2 virus is increasingly being identified in children termed Multisystem Inflammatory Syndrome in Children (MIS-C) and more recently in adults(MIS-A). Due to its clinical similarity with Kawasaki Disease, some institutions have used intravenous immunoglobulins and steroids as first line agents in the management of the disease. We seek to find how effective intravenous immunoglobulin therapy is across these two disease entities. A comprehensive English literature search was conducted across PubMed, MEDLINE, and EMBASE databases using the keywords multisystem inflammatory syndrome in children/adults and treatment. All major online libraries concerning the diagnosis and treatment of MIS-C and MIS-A were searched. Relevant papers were read, reviewed, and analyzed. The use of intravenous immunoglobulins (IVIG) and steroids for the treatment of multisystemic inflammatory syndrome in children(MIS-C) is well established and recommended by multiple pediatric governing institutions. However, there is still no optimal treatment guideline or consensus on the use of IVIG in adults. The use of IVIG in both the child and adult populations may lower the risk of treatment failure and the need for adjunctive immunomodulatory therapy. Despite the promising results of IVIG use for the management of MIS-C and MIS-A, considering the pathophysiological differences between MIS-C and MIS-A, healthcare professionals need to further assess the differences in disease risk and treatment. The optimal dose, frequency, and duration of treatment are still unknown, more research is needed to establish treatment guidelines.